High parathyroid hormone levels are associated with osteosarcopenia in older individuals with a history of falling. (July 2018) - Suriyaarachchi, Pushpa; Gomez, Fernando; Curcio, Carmen L.; Boersma, Derek; Murthy, Lavanya; Grill, Vivian; Duque, Gustavo
Highlights: Osteosarcopenia defines a diagnostic subset of individuals at higher risk of falls, fractures and institutionalization. There is an independent association between high levels of parathyroid hormone and osteosarcopenia. Our results suggest an important role of parathyroid hormone in osteosarcopenia that deserves further exploration. Abstract: Objectives: The combination of osteopenia/osteoporosis and sarcopenia (osteosarcopenia) defines a diagnostic subset of individuals at higher risk of falls, fractures and institutionalization. In this study we aimed to assess the potential role of high serum levels of parathyroid hormone (PTH) in osteosarcopenia. We hypothesized that a high PTH level is one of the major determinants of this syndrome. Study design: Cross-sectional study in 400 subjects (mean age = 79, 65% women) assessed between 2009 and 2014 at the Falls and Fractures Clinic, Nepean Hospital (Penrith, Australia). Main outcome measures: Medical history, physical examination, bone densitometry, body composition, posturography, grip strength, gait parameters, and blood tests for nutrition and secondary causes of sarcopenia and osteoporosis. Patients were assigned to one of four groups: 1) osteopenic/osteoporotic; 2) sarcopenic; 3) osteosarcopenic; or 4) non-sarcopenic/non-osteopenic. Patients with abnormal corrected calcium levels were excluded from analysis. Between-group differences were assessed using one-way analysis of variance and chi-squared tests. Multivariable linear regression was used to evaluate the association between the groups and PTH levels adjusted for age, vitamin D, renal function and albumin. Results: 24% of the subjects had a high serum PTH level with normal corrected calcium level. These subjects were older, reported more falls per year, and had lower grip strength, limits of stability, BMD, and gait velocity. Subjects with high PTH levels were more likely to be in the osteosarcopenia group than in the non-sarcopenic/non-osteopenic group (OR 6.88; CI: 1.9–9.2). Conclusions: We reported an independent association between high PTH levels and osteosarcopenia. Our results suggest an important role of PTH in osteosarcopenia that deserves further exploration.